Minimising UMP in DFIGs. Issue 17 (20th May 2019) - Chuan, Hawwooi; Shek, Jonathan K.H.
Abstract : The doubly fed induction generator (DFIG) has become increasingly popular for variable speed wind turbines because of the lower power electronics converter rating required. However, the small air gap of a DFIG causes it to be vulnerable to slight misalignment of the rotor which may cause a large unbalanced magnetic pull (UMP) to be exerted on the bearings. The reliability of the generator is important to reduce revenue loss; this is especially the case for generators in offshore wind turbines where minimising the cost of energy is crucial in completing with more established forms of electricity generation. This study has proposed the usage of stator damper windings to reduce the UMP. An example of a four‐pole DFIG with static eccentricity is shown where finite element analysis is used to verify the UMP for cases with and without damper windings. Finally, additional losses due to rotor eccentricity are discussed.